Analisa Pengendalian Proyek Menggunakan Metode Nilai Hasil pada Pembangunan Kantor PT. Waruna - Purba, Leonardo; Ardan, Melloukey; Rangkuti, Nuril Mahda (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2024)
This study uses the method of value results (Earned Value). This study aims to determine or predict how much the cost of a project at the time of implementation and to determine the effectiveness of project control and to determine the efficiency of resource users in the form of Cost Performance Index (CPI) and Schedule Performance Index (SPI) as well as total project cost forecasts (EAC). To analyze project control, there are three parameters or indicators, namely BCWS (Budgeted Cost of Work Schedule), BCWP (Budgeted Cost of Work Performed), ACWP (Actual Cost of Work Performed). Delays and deviations can be identified by looking at the Cost Variant (CV) and Schedule Variant (SV). In the calculation of the concept, the value of the SV = -6.197.845.000 value (-) indicates that the work is running slower than the planned schedule, while the CV value = -232.750 value (-) indicates the work costs more than the budget provided. By calculating the estimated total project cost (EAC) of Rp. 15,755.722,795 while the RAB value is Rp. 15,345,000,000. this means that at the end of the project it is estimated that there will be a cost overrun of Rp.410.722.792 (2.67% of RAB).